2017
DOI: 10.1080/07256868.2017.1410111
|View full text |Cite
|
Sign up to set email alerts
|

‘Who Are Diverse?’ Conceptualisations of Cultural Diversity in Schools behind Desks and at Chalkface

Abstract: This paper analyses the meanings and values attached to 'cultural diversity' as a descriptive and interpretative category in the field of education in Spain, including its application to define different groups in elementary and primary schools there. It reports from a comparative study that considers the discursive production of 'cultural diversity' in Spanish academia together with the discourse of teaching staff from three schools with specific programmes aimed at cultural diversity. Results attest to three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…While the concept of diversity is widespread in the discourses, practices, and policies of governments, educational institutions, businesses, academic institutions, and social organisations (García-Cano et al, 2018), the debate 1 The study reported in this paper was supported by the Spain's Ministry of Economy, Industry, and Competitiveness, the State Research Agency, and the European Regional Development Fund (grant number EDU2017-82862-R).…”
Section: Introductionmentioning
confidence: 99%
“…While the concept of diversity is widespread in the discourses, practices, and policies of governments, educational institutions, businesses, academic institutions, and social organisations (García-Cano et al, 2018), the debate 1 The study reported in this paper was supported by the Spain's Ministry of Economy, Industry, and Competitiveness, the State Research Agency, and the European Regional Development Fund (grant number EDU2017-82862-R).…”
Section: Introductionmentioning
confidence: 99%
“…The Caucasian group, majoritarian in Spain, identifies cultural diversity in schools only with the arrival of the third group since the 1990s (Andrés & Giró, 2020;García-Cano et al, 2018;Garreta, 2006;Garreta et al, 2020). This fact gives rise to a 'problematic categorisation' (García-Cano et al, 2018) that evidences 'educational policy as an act of white supremacy' (Gillborn, 2005; see also Fylkesnes, 2019), since there is on the part of Spanish academics, an appropriation of a discourse that is of Anglo-Saxon origin and links cultural diversity with migration. This result sets it apart from the construction of cultural diversity in other contexts, such as the US, where cultural diversity is often a euphemism for race and refers to how minority racial groups differ from the white population (García-Cano et al, 2018, p. 79).…”
Section: The State Of the Artmentioning
confidence: 99%
“…The fight against racial discrimination is then called 'promotion of diversity' (García-Cano et al, 2018). The problem is that, lying behind this managerial rhetoric, the demand for -structural-equality may be diluted in -identity-diversity (Duru-Bellat, 2011;Laufer, 2009, cf.…”
Section: Theoretical Framementioning
confidence: 99%
See 2 more Smart Citations